GINGIVAL MELANOSIS: CUNIcAL CASE REPORT - García Linares, Sixto (2004)
It is reported a clmical case of gingival melanosis in a female 16 years old patient. Etiology fisiopatllOlogy and treatment are discussed. It is described which technique is performed in tlús patient using rotatory media and second intention healing. Gingival melanosis is an anatoinical variation, which could be reported with high frequency in our country.